(untitled) (ENTHYMEMA, 2025)
This article presents some synthetic reflections on the notion of rhythm developed in Yuri Tynianov’s The Problem of Verse Language (1924), with particular attention to the relationship between the conception of the work unity and its peculiar space-time configuration, the status of flow and energy, the role of reception, and the copresence of the motoric and the phenomenological approaches.